Pharmacotherapy of retinal disease with visual cycle modulators. (24th March 2018) - Hussain, Rehan M.; Gregori, Ninel Z.; Ciulla, Thomas A.; Lam, Byron L.
ABSTRACT: Introduction : Pharmacotherapy with visual cycle modulators (VCMs) is under investigation for retinitis pigmentosa (RP), Leber congenital amaurosis (LCA), Stargardt macular dystrophy (SMD) and nonexudative age-related macular degeneration (AMD), all blinding diseases that lack effective treatment options. Areas covered : The authors review investigational VCMs, including oral retinoids, 9-cis-retinyl-acetate (zuretinol) and 9-cis-β-carotene, which restore 11-cis-retinal levels in RP and LCA caused by LRAT and RPE65 gene mutations, and may improve visual acuity and visual fields. Therapies for SMD aiming to decrease accumulation of toxic Vitamin A dimers and lipofuscin in the retina and retinal pigment epithelium (RPE) include C20-D3-vitamin A (ALK-001), isotretinoin, VM200, emixustat, and A1120. Mouse models of SMD show promising data for these treatments, though proof of efficacy in humans is currently lacking. Fenretinide and emixustat are investigational VCMs for dry AMD, though neither has been shown to reduce geographic atrophy or improve vision in human trials. A1120 prevents retinol transport into the RPE and may spare the side effects typically seen in VCMs (nyctalopia and chromatopsia) per mouse studies. Expert opinion : Oral VCMs may be feasible treatment options for degenerative retinal diseases based on pre-clinical and some early clinical studies. Further trials are warranted to assess their efficacy and safety in humans.